Sustainable Crowd Funding Solutions Using Blockchain Technology - Suganya, P.; Mega, S.; A. Thaheen Zareen, B.; Tharani, J.; Karkatesh, Karkatesh (Journal of Neonatal Surgery, 2025)
Abstract Although funding is important in today's society, the Proof of Work (PoW) algorithm, which lacks transparency and data immutability, is frequently used in the systems that now manage donations for NGOs. A decentralized funding system utilizing blockchain technology and the Proof of Stake (PoS) algorithm is suggested as a solution to these issues. Through this system, students can post their financial or resource requirements, charities can publish their needs, and anyone with business ideas can submit their applications. A clear and effective financing procedure is ensured by donors' ability to view these needs and make direct contributions. Every transaction is safely documented by utilizing blockchain technology, which offers data immutability and guards against unwanted changes.Compared to PoW, the PoS algorithm guarantees a quicker and more effective transaction validation process, improves security, and uses less energy. By removing middlemen, this system not only increases confidence between donors and receivers but also expedites the funding process. In the end, the suggested funding management system improves accessibility to financial aid and resources by providing a dependable solution for assisting startups, students, and nonprofit organizations with increased transparency, security, and efficiency